Quality Evaluation and Quantification of Caffeic Acid in Orthosiphon aristatus Collected from Oudomxay, Vientiane Capital, and Champasak Provinces, Lao PDR - Kingkeo, Alounny; Phakeovilay, Chiobouaphong; Sorsavanh, Souphaphone; Kongmany, Santi; Chanthavong, Oudone; Lanorsavanh, Soulivanh; Douangdeuane, Bounleuane (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Orthosiphon aristatus (Blume) Miq., (O. aristatus) commonly known as cat’s whiskers, is a traditional medicinal plant in the Lao People’s Democratic Republic (Lao PDR), widely recognized in local pharmacopeia for its therapeutic properties in maintaining health and treating ailments such as urinary tract infections, diabetes, arthritis, gout, kidney disorders, hypertension, diuresis, and edema. Among its bioactive constituents, polyphenolic compounds such as caffeic acid are considered key biomarkers with diverse pharmacological activities including antiviral, anticancer, anti-inflammatory, and antioxidant effects. However, scientific data concerning the phytochemical composition and quality evaluation of O. aristatus in Lao PDR remain limited. Therefore, this study aimed to assess the quality parameters of raw materials and determine the content of caffeic acid in O. aristatus samples collected from Oudomxay, Vientiane Capital, and Champasak provinces. Nine samples were evaluated following the Thai Herbal Pharmacopoeia (THP) standards, including tests for foreign matter, total ash, acid-insoluble ash, moisture content, and extractive values. Quantitative analysis of caffeic acid (mg/kg dry weight) was performed using UHPLC-PDA under isocratic conditions (0.2% formic acid in water:methanol, 60:40, flow rate 1.0 mL/min) with a C18 reverse-phase column at 40 °C and detection at 325 nm. The results showed that the quality parameters of all samples met the THP standards: foreign matter (0.43–0.75%), total ash (7.75–8.60%), acid-insoluble ash (0.58–0.59%), and moisture content (0.10–0.39%). The water and ethanol extractive values ranged from 25.34–25.90% and 10.44–11.61%, respectively. The caffeic acid content was 4.66 mg/kg in samples from Oudomxay and Vientiane Capital, and 6.35 mg/kg in samples from Champasak, with no statistically significant difference (p > 0.05). This study provides essential baseline data for quality control and assurance of O. aristatus-based herbal products in Lao PDR.